2000
DOI: 10.1021/ja001676x
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of Substrate and Inhibitor Complexes with AmpC β-Lactamase:  Possible Implications for Substrate-Assisted Catalysis

Abstract: Group I β-lactamases are major resistance determinants to β-lactam antibiotics. Despite intense study, the identity of the catalytic base, the direction of hydrolytic attack, and the functional difference between β-lactam substrates and β-lactam inhibitors remain controversial. To explore these questions, we determined the X-ray crystal structures of several representative β-lactams in their acyl−adduct complexes with the group I β-lactamase AmpC. A complex with the substrate loracarbef and a deacylation-defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
172
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 92 publications
(192 citation statements)
references
References 52 publications
20
172
0
Order By: Relevance
“…these residues, as observed in the complexes of AmpC with 6, 8, and 12 20,24,26 (Table 1; Figure 3C). In the complexes of AmpC with the -lactams 10 and 13, the carbacephem and oxacephem rings, respectively, interact with the leucines.…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…these residues, as observed in the complexes of AmpC with 6, 8, and 12 20,24,26 (Table 1; Figure 3C). In the complexes of AmpC with the -lactams 10 and 13, the carbacephem and oxacephem rings, respectively, interact with the leucines.…”
Section: Resultssupporting
confidence: 65%
“…In this structure, the carboxylate also hydrogen bonds with Thr316. 20 In the AmpC/13 (moxalactam) complex, the C4 carboxylate hydrogen bonds directly with Asn289 and Asn346 and interacts, via water molecules, with Asn343 and Arg349. 20 None of the computational programs were used to predict carboxylate binding sites on AmpC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 The proton on the Tyr150 Oη is collinear with the position of the lactam nitrogen on the other side of the boronic O2 atom and 2.63 Å away from the O2 atom. The tyrosine proton is thus well placed to stabilize developing negative charge on the deacylating water, while the substrate nitrogen acts as a base, transiently accepting the proton from the other side.…”
Section: Discussionmentioning
confidence: 99%
“…7,21,29 In the deacylation transition state, analogous to this structure, it has been suggested that Lys67 can cooperate with Tyr150, either stabilizing a tyrosinate base or accepting a proton from the hydrolytic water by way of the tyrosine. 24,25 In either scenario, Lys67 might be expected to hydrogen bond with Tyr150.…”
Section: Lys67mentioning
confidence: 98%